High-definition abdominal liposuction with silicone tubing - Rogerio Schützler Gomes; Carlo Mognon Mattiello; Natalia Biancha Rendon; Elvio Bueno Garcia; Heitor Francisco Carvalho Gomes; Lydia Masako Ferreira (Revista Brasileira de Cirurgia Plástica)
Introduction: Recently, some authors have described high definition liposuction in the abdominal region, achieved by the vigorous marking of the grooves of the linea alba, linea semilunaris, and transverse tendinous intersections within the rectus abdominis muscle. The aim is to present a pilot study of high-definition abdominal liposuction technique using conventional material and silicone tubing in the dressings . Methods: Twenty cases were submitted to conventional liposuction, followed by superficial liposuction under the linea alba, linea semilunaris, and tendinous intersections, until a groove was formed at these sites. Flexible silicone tubing was externally fixed with Micropore tape in the linea alba, bilateral linea semilunaris, and tendinous intersections, and removed after 5 days. Results: A mean increase of 20 minutes was required to perform these steps. The marks of the silicone tubing were evident at the first follow-up, and less prominent at the second follow-up. No color change, ischemia, or significant pain was observed using this technique. After 3 months, there were no cases of dermatitis, cutis marmorata, seroma, infection, contour irregularity or need for additional procedures. Conclusion: High-definition abdominal liposuction was performed using conventional materials and externally fixed temporary silicone tubing.